2003
DOI: 10.2746/042516403775467405
|View full text |Cite
|
Sign up to set email alerts
|

Dystocia in a referral hospital setting: approach and results

Abstract: Summary Reasons for performing study: Dystocia in the mare is an emergency in which duration has a profound effect on survival of the foal. Specific examination of the effects of dystocia duration on foal survival provides information to enable horse care personnel and veterinarians to manage these cases more effectively and maximise the chances of obtaining a live foal. Hypothesis: Dystocia duration would have a negative impact on foal survival while method of dystocia resolution would not have an effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
51
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 5 publications
(14 reference statements)
14
51
1
11
Order By: Relevance
“…This percentage was slightly higher than those described in 3 other studies (30% to 31%) 1,4,8 and was substantially higher than those reported by some groups (5% to 10%). This percentage was slightly higher than those described in 3 other studies (30% to 31%) 1,4,8 and was substantially higher than those reported by some groups (5% to 10%).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This percentage was slightly higher than those described in 3 other studies (30% to 31%) 1,4,8 and was substantially higher than those reported by some groups (5% to 10%). This percentage was slightly higher than those described in 3 other studies (30% to 31%) 1,4,8 and was substantially higher than those reported by some groups (5% to 10%).…”
Section: Discussioncontrasting
confidence: 66%
“…Causes of death for these 4 mares included uterine artery rupture (n = 2), uterine wall rupture (1), and postoperative complications after jejunal cecostomy performed after the foal was delivered because of a tear in the gastrosplenic ligament (1). Causes of death for these 4 mares included uterine artery rupture (n = 2), uterine wall rupture (1), and postoperative complications after jejunal cecostomy performed after the foal was delivered because of a tear in the gastrosplenic ligament (1).…”
Section: Breed Maternal Age and Pregnancy Variables-mentioning
confidence: 99%
“…(2007) recently reported that every 10 min increase in the duration of Stage II labour beyond 30 min was associated with a 10% increase in the existing risk of a foal being born dead, and a 16% increased risk of the foal not surviving to discharge. Byron et al . (2002) further noted that the interval from rupture of the chorioallantoic membrane to delivery of the fetus was 13.6 min shorter for foals that were born alive and survived to discharge than for foals born dead or that did not survive to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Dystocia in horses [5] and prolonged labor in humans [10] and cattle [14] are associated with neonatal acidosis. Prolonged equine labor is associated with fetal asphyxia, hypoxia, and a higher risk of foal mortality; thus, early recognition and assistance are important in cases of dystocia [1, 4]. Stage II of labor (from rupture of the chorioallantois to completion of delivery) takes less than 2 hr in humans [8] and 2–3 hr in cattle [13].…”
mentioning
confidence: 99%